Local orders and armed conflict. a methodology compared (2014)
The research question is how the local orders in the Territories larger armed conflict in Colombia are reconfigured and the possible underlying reasons for this reconfiguration, between 1991 and 2010. This article presents the conceptual and methodological frameworks built specifically for this research under the parameters of a comparative methodology. Here we present the problem and the research approach, the proposed typology for comparing local orders in the conflict and the procedure for possible explanations of local trajectories in the framework of the typology. Finally, we present the comparative results obtained from this methodology and the prospects that this experience left open for future research are presented.